O tempo da religião no espaço escolar: a história do ensino religioso no colégio Santa Cruz - Silva, Nilma Paula Combas da (2018)
The dissertation presents a research on the history of Religious Education of the Santa Cruz College, catholic, private and pluralist, located in Alto de Pinheiros in São Paulo, as a case study. This College was maintained by the Congregation of the Holy Cross, which originated in France, and was founded by priests of the Congregation established in Canada. With this aim, a survey of historical documents and bibliography on the subject is done, to investigate the process of development of the discipline of Religious Education. Passing on the foundation of the Congregation, its founder and the historical context that this happens, the arrival of the Canadian priests in Brazil and the foundation of the College. There is also a contextualization of the wider Religious Education in Brazil and as it happened in the College. There is the suggestion of Phases of this Religious Education, and the description of the current Model, which is epistemologically based on the Science of Religion. How was the origin and the routing guidelines of the same. That goes against the humanist and pluralist philosophy that the College has followed since its foundation. So that there is the integral formation of the human being